European Union regulations reporting corporate development towards green transformation. - Kamiński, Ryszard (Луцьк : Вежа-Друк, 2023)
The experience gained over the past few years by non-financial information reporters and their stakeholders has made it possible to review existing regulations in terms of achieving the goals they set out to achieve when they were enacted, and in the context of the emergence of new circumstances of business operations and new challenges facing society and the economy, particularly those related to the provisions of the European Green Deal [1]. This led to the recognition that a change in the system of reporting on environmental and social issues by companies was necessary. This position resulted in the adoption of the Corporate Sustainability Reporting Directive EU/2022/2464 (CSRD for short) by the Parliament and Council of the European Union [2]. The directive is linked to a number of European Commission regulations enacted between 2019 and 2022, primarily on environmental and climate issues. This situation inspired the preparation of this study. Its purpose is to present the assumptions of the aforementioned directive and related regulations, and to evaluate these legal acts. The study was prepared on the basis of the literature on the subject and legal acts. The method of critical analysis of source texts, including legal texts, and the comparative method were used.
Keywords: sustainability; non-financial reporting; taxonomy; European Green Deal